Carbon footprint analysis of sweet sorghum-based bioethanol production in the potential saline - Alkali land of northwest China. (15th May 2022) - Shi, Xinjie; Xiong, Jinran; Yang, Xiaolin; Siddique, Kadambot H.M.; Du, Taisheng
Abstract: Available saline-alkali land could be used to plant bioenergy crops for biofuel stocks, retaining productive land for food crops. Sweet sorghum is a promising candidate for bioethanol production due to its ability to tolerate environmental stresses. This study estimated the available saline-alkali land for sweet sorghum planting in northwest China using a multi-factorial analysis, quantified its bioethanol potential, and assessed the carbon footprint of sweet sorghum stalk (SSS)-based bioethanol production on this land using a life cycle assessment. The results revealed 9.33 × 10 5  ha saline-alkali land available for sweet sorghum planting, or 11.47% of the total saline-alkali land in the study area, with a potential yield of 6.87 × 10 7  t sweet sorghum stalk, producing 4.29 × 10 6  t bioethanol. The carbon footprint of SSS-based bioethanol production ranged from 2.21 to 2.25 t CO2 eq t −1 bioethanol across selected districts. Sweet sorghum cultivation accounted for most of the carbon footprint in each district (40.18–45.30%). Compared to gasoline, the carbon footprint for pure bioethanol (E100) made from SSS in the selected districts declined by 33.42–49.94% with or without reusing the bagasse co-product. The carbon footprint of E10 (10% bioethanol from SSS and 90% gasoline) declined by 2.68–4.49%. Thus, it is possible to cultivate sweet sorghum on the selected saline-alkali land in northwest China for bioethanol production. However, future studies are needed to (1) improve sweet sorghum genotypes and identify optimal agronomic management for feedstock, (2) advance technologies for bioethanol production, (3) develop bioethanol-tolerant yeast and bacteria strains, and (4) stimulate policy support for growers and industrialists to accelerate cleaner production. Highlights: The available saline-alkali land for sweet sorghum planting in northwest China was assessed. Carbon footprint and potential yield of sweet sorghum stalk-based bioethanol was evaluated. SSS-based bioethanol decreased carbon footprint up to 49.94% compared to gasoline.